Avenues of agri-business entrepreneurship in India - Bhooshan, Neeru; Sharma, Akriti (Indian Farming, 2021)
The agribusiness word integrates two different yet cohesive domains that have various gears to make it compatible with each other. The economic activities that are derived from or connected to farm products and its supply chain are often named as Agribusiness. In India, agriculture is one of the principle economic activities that are carried out by majority of the population. Employing the widest population base, agriculture is the main source of income for many living below poverty line. It may play a significant role in alleviating poverty if done with utmost precision with optimum utilization of resources along with least wastages. Thus, a lot of intervention and investments are needed to ensure a sustainable livelihood for many people employed in agriculture. India has a rich biodiversity in its account, making it one of the largest producers of many commodities across the globe. At the same time, this diversity in the landforms, soils, crops, cropping patterns along with cultural and demographic variability of the manpower carrying out the farming and related operations creates few unstandardized protocols and inefficient value chains. The poor yet developing infrastructure is one of the biggest hurdles in realization of the maximum efficiency of these operations. Due to perishability of the produce, wastages during handling is another issue that creates a heavy burden on the economy. Improvement in productivity becomes an important factor for the country’s food security in the light of the constrained availability of agricultural land.